THE EFFECT OF COMBINATION OF CHICKEN MANURE AND KCl ON THE GROWTH AND YIELD OF SHALLOT ON ALUVIAL SOIL - kizie, murni (Fakultas Pertanian Universitas Tanjungpura, 2019)
Shallots (Allium ascalonicum L.) is a horticultural commodity classified as spice vegetables which has many benefits and high economic value. Efforts to increase the production of shallots in West Kalimantan can be carried out on various types of soil, including alluvial soils. The purpose of this research was to obtain the best dose combination of chicken manure with KCl on the growth and yield of shallots on alluvial soil. The study was conducted in the village of Parit Bugis, Segedong District, Mempawah Regency. The study began on May 21 2018 to August 19 2018. This study used a Completely Randomized Design (CRD) consisting of 5 treatment levels, namely A = 50 g / chicken manure plants equivalent to 10 tons / ha and 1.5 g KCl / plants equivalent to 300 kg / ha, B = 75 g / chicken manure plants equivalent to 15 tons / ha and 1.25 g KCl /plants equivalent to 250 kg / ha, C = 100 g / chicken manure plants equivalent to 20 ton / ha and 1 g KCl / plant equivalent to 200 kg / ha, D = 125 g / chicken manure plants equivalent to 25 tons / ha and 0.75 g KCl / plant equivalent to 150 kg / ha, E = 150 g / chicken manure crops equivalent to 30 tons / ha and 0.5 g KCl / plants equivalent to 100 kg / ha. Each treatment was repeated 5 times and each replication consisted of 3 sample plants so that the plants totaled 75 plants. The variables observed in this study were plant height (cm), number of leaves per clump (strands), number of tubers per clump (fruit), fresh weight of tubers per clump (g), dry weight of tubers per clump (g). The results showed that the combination of chicken manure and KCl gave an unreal effect on all observation variables.Keywords: alluvial, chicken manure and KCl, Shallot.